Executive's guide to web services - Marks, Eric A. (John Wiley & Sons, 2003)
Chapters include: Standards, Concepts, and Terminology; Web Services Adoption; Strategic Perspective of Web Services; Vertical Market Perspective of Web Services; Architecting for Competitive Advantage; Web Services Vendor Landscape.